POLA ASUH ORANG TUA DALAM PENANAMAN KARAKTER ANAK DI SDN BAGUS 2 MARABAHAN - Cahyani, Irni; Wulandari, Arina; Zaleha, Siti (Universitas Sulawesi Tenggara, 2024)
Parenting patterns are a model or way of behaving that is applied in a family environment to protect and care for children by parents who are the first educators for the children themselves in the family itself. Parenting patterns are divided into three types of parenting patterns, namely authoritarian parenting patterns, democratic parenting patterns, and permissive parenting patterns. From there, parents apply one of these parenting patterns in the family to educate children in character building so that children have noble character. This study aims to determine how parenting patterns are in building children's character and the obstacles in implementing parenting patterns in children at SDN Bagus 2 Marabahan. The research method used in this study is qualitative research, which uses data collection techniques in the form of interviews, observations, and documentation. Testing the validity of the data using triangulation with the subjects studied being parents of students who attend SDN Bagus 2 Marabahan. This research was conducted in Bagus Village, Jalan S. Parman RT. 006, Marabahan District. The results of the study showed that the parenting patterns applied in instilling the character of Pancasila student profiles at SDN Bagus 2 Marabahan, 1) the character of faith, devotion to God Almighty and noble morals tends to be democratic, but sometimes in certain situations it can change to authoritarian. 2) Independent characters tend to use democratic parenting patterns. 3) The character of mutual cooperation, parents use more democratic parenting patterns. 4) Creative characters, the parenting patterns applied by parents to children are permissive parenting patterns. 5) Global diversity characters use more permissive parenting patterns, but at certain times it can change to democratic parenting patterns. 6) Critical reasoning characters, use permissive parenting. The obstacles faced by parents while educating children at home are lack of communication with children, lack of free time to educate children, and the level of education taken by parents, most parents only have elementary/junior high school education.